2019
DOI: 10.3390/molecules24122283
|View full text |Cite
|
Sign up to set email alerts
|

Development of Technetium-99m-Labeled BODIPY-Based Probes Targeting Lipid Droplets Toward the Diagnosis of Hyperlipidemia-Related Diseases

Abstract: Hyperlipidemia causes systemic lipid disorder, which leads to hepatic steatosis and atherosclerosis. Thus, it is necessary to detect these syndromes early and precisely to improve prognosis. In the affected regions, abnormal formation and growth of lipid droplets is observed; therefore, lipid droplets may be a suitable target for the diagnosis of hyperlipidemia-related syndromes. In this study, we designed and synthesized [99mTc]Tc-BOD and [99mTc]Tc-MBOD composed of one technetium-99m and two BODIPY scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In general, the Ham group structure is known to have two tautomer, and thus the 99m Tc-Ham complex forms two tautomer which can be observed by RP-HPLC 7 . The chelation of Ham and 99m Tc was confirmed by the disappearance of the peak from 99m TcO 4 - (retention time: 2–4 min 11 ) and then the appearance of two peaks because it is difficult to synthesize the analogues of the rhenium-Ham complex 7 . To search for an appropriate 99m Tc radiolabeling reaction condition, we first evaluated the reaction of Ham-Cys and 99m TcO 4 - with different concentrations of Ham-Cys (final concentration: 10 and 20 mM) in different solvents [phosphate buffer (pH 7.4) and acetic acid/ethanol = 1/4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the Ham group structure is known to have two tautomer, and thus the 99m Tc-Ham complex forms two tautomer which can be observed by RP-HPLC 7 . The chelation of Ham and 99m Tc was confirmed by the disappearance of the peak from 99m TcO 4 - (retention time: 2–4 min 11 ) and then the appearance of two peaks because it is difficult to synthesize the analogues of the rhenium-Ham complex 7 . To search for an appropriate 99m Tc radiolabeling reaction condition, we first evaluated the reaction of Ham-Cys and 99m TcO 4 - with different concentrations of Ham-Cys (final concentration: 10 and 20 mM) in different solvents [phosphate buffer (pH 7.4) and acetic acid/ethanol = 1/4].…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated the in vitro stability of 99m Tc-(Ham-RGD) 2 in mouse plasma; however, we found that the radiochemical purity decreased in a time dependent manner, and some unknown hydrophilic metabolites emerged (Figure S2 ). Given that other Ham-based 99m Tc radiolabeled compounds we developed previously 11 , 13 showed high stability in plasma and good blood clearance, it is suspected that those unknown metabolites affected the slow blood clearance. Although the metabolites and the reason of the instability is still unclear, the low stability of 99m Tc-(Ham-RGD) 2 in plasma is the limitation, and further study for redesigning the bifunctional chelate to improve the stability would be needed for use it in in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the Ham group structure is known to have two tautomer, and thus the 99m Tc-Ham complex forms two tautomer which can be observed by RP-HPLC 7 . The chelation of Ham and 99m Tc was con rmed by the disappearance of the peak from [ 99m Tc]NaTcO 4 (retention time: 2-4 min 11 ) and then the appearance of two peaks because it is di cult to synthesize the analogues of the rhenium-Ham complex 7 . To search for an appropriate 99m Tc radiolabeling reaction condition, we rst evaluated the reaction of Ham-Cys and [ 99m Tc]NaTcO 4 with different concentrations of Ham-Cys ( nal concentration: 10 and 20 mM) in different solvents [phosphate buffer (pH 7.4) and acetic acid/ethanol = 1/4].…”
Section: Discussionmentioning
confidence: 99%
“…To search for an appropriate 99m Tc radiolabeling reaction condition, we rst evaluated the reaction of Ham-Cys and [ 99m Tc]NaTcO 4 with different concentrations of Ham-Cys ( nal concentration: 10 and 20 mM) in different solvents [phosphate buffer (pH 7.4) and acetic acid/ethanol = 1/4]. In our previous study, we used an acetic acid/ethanol mixture as the solvent for 99m Tc radiolabeling reactions of compounds containing Ham [9][10][11][12][13] ; however, the radiochemical yields were low [10.4 ± 9.8% ( nal concentration of Ham-Cys:10 mM), 11.0 ± 5.0% (20 mM)] (Table 1) and the acquired 99m Tc-radiolabeled compound was unstable. On the other hand, 99m Tc radiolabeling reaction to give [ 99m Tc]Tc-(Ham-Cys) 2 in phosphate buffer (pH 7.4) proceeded with radiochemical yields of 68.7 ± 2.4% ( nal concentration of Ham-Cys: 10 mM) and 75.3 ± 4.5% (20 mM) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation